THE EFFECT OF ONLINE LEARNING ON STUDENTS ABILITY IN ENGLISH READING SKILL IN SMA SWADARMA WERDHI AGUNG - I Kadek Andi Putra; Noldy Pelenkahu; Nihta Liando (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to find out whether the online learning can improve students reading skill by using WhatsApp applications or not. Online learning means learning that is done online, using a variety of learning applications and social networks. The researcher used pre-experimental research and the sample of this research is the eleventh grade students of SMA Swadharma Werdhi Agung which consist of 20 students. The technique of data collecting used was measurement technique and tool of data collecting was multiple choice, matching and true or false. As well as providing a questionnaire to see student’s opinions about the WhatsApp applications as a medium in online learning. The data were calculated with the result of students’ pre-test was 55 and post-test was 81. The students’ different score between pre-test and post-test was 26. As the result, taught online learning during pandemic by using WhatsApp applications by providing narrative text was highly effective in terms of increasing the students’ mean score of narrative text reading skill.